Meningkatkan hasil belajar dan aktivitas belajar siswa dengan metode think pair share pada materi bangun ruang kubus kelas V di SDN Baturetno 02 Desa Baturetno Kecamatan Singosari - Nurfiani, Hanidah Aulia (Maliki Interdisciplinary Journal, 2024)
Mathematics learning at SDN Baturetno 02 often uses a one-way learning method, which means the teacher explains more than invites discussion. Occasionally there is a question and answer session, but students are reluctant to ask questions, maybe only one or two people ask. Learning like this is considered very unattractive and less efficient. To overcome these problems, the Think Pair Share (TPS) learning method was applied. This study aims to increase student learning outcomes and learning activities through the Think Pair Share learning method. This research was conducted by pre-test and post-test as well as control group discussion forums. For pre-test and post-test questions to find out student learning outcomes after and before the Think Pair Share method is applied, while for student learning activities using observational analysis during class learning. The material presented regarding cubic shapes starts looking for side lengths, volumes, and making nets. The results of the study show that learning outcomes improve more, as can be seen from the post-test scores which are better than the pre-test. Learning activities have also greatly increased, because students can enjoy learning more in class.